SOSIALISASI LITERASI MANAJEMEN KEUANGAN DAN BISNIS DIGITAL PADA PEKERJA WANITA INDONESIA DI MALAYSIA - Kamarudin, Anna Permatasari; Ratnawati, Ratnawati; Erna, Erna; Amiruddin, Amiruddin; Fatma, Mawarni; Diana, Rahma; Khairani, Elisa; Basyirah, Basyirah; Zainudin, Zainudin; Amna, Amna (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Financial literacy ic very important. Financial management literacy is closey related to improving welfare. Knowledge of financial management literacy can be developed into a digital business. The purpose of this Community Service is to. These two things have been conveyed to manufacturing worlers in Selangor, Malaysia. The number of workers participating in thus program is 15 people. The purpose of thus PkM is to make the workers ‘knowledge better in financial management and to know the use of the income earned for useful things, especially after workers return to the country, one of which is with digital business. The implementastion method carried out is the Planning Stage, including communicating with related parties carried out online, the Preparation Stage which consists of the preparation Stage with introduction dissemination of The Pre-Test, sosializzation and lectures, question and answer, Post-Test and ended with filling out and evaluation of the activity assessment. The results of the program show that there has been an increase in knowledge among workers. The evaluation of the workers given in the form of a review of the PkM team was good, where 2 out of statement given showed that the workers ‘strongly agreed; as much as 100% that the event was in accordance with the theme and material provided. The workers participated in this program with enthusiasm. Meanwhile, the socialization statement was in accordance with the theme, the socialization was useful and the workers satisfaction 66,3% assessment